Human Relationship with Nature: A Metaphor-Ecolinguistic Perspective in The Lyrics of Shalawat Badar by KH Ali Manshur - Al Bahar, Ali Hasan; Suparno, Darsita; Rokhim, Minatur; Pallawagau, Baso; Sanjani, Muhamad Ali Raaf; Rifdha Shahira, Tasya (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
This study examines the conceptual metaphor in the lyrics of Shalawat Badar by KH Ali Manshur which represents the socio-ecological experience in the tradition of pesantren and Nahdlatul Ulama. With a qualitative descriptive method, data was taken from 30 lines of lyrics that contained metaphorical expressions at the level of words, phrases, and clauses. Data were collected through documentation, careful reading, and logging, then analyzed with cognitive semantic theory, Lakoff and Johnson’s conceptual metaphor framework, ecolinguistic approaches, and theme-rema analysis. The results of the study found 17 structural metaphors, 6 orientational metaphors, and 7 ontological metaphors related to the themes of social struggle, politics, religious education, prayer and supplication, the symbols of Nahdlatul Ulama, and the integration of the Al-Barzanji ritual in Java. From an ecolinguistic perspective, lexicons such as "plague" and "disaster" are read as linguistic traces of the environmental and health crises of the 1960s, particularly the outbreak of diseases such as leprosy and filariasis, thus showing the variety of religious discourses that hold ecological memories. Structural metaphors position the Prophet Muhammad as a mediative bridge that connects Muslim communities affected by plagues and socio-political crises with divine protection, while orientational metaphors map spatial experiences into emotional and spiritual states. Ontological metaphors show the way in which abstract divine agency is understood through concrete objects and events, and the theme–rema pattern highlights the marked and unmarked themes that advance the narrative of crisis and hope. This research is significant because it expands the study of conceptual metaphors that are integrated with ecolinguistics in the religious salawat text in the very popular tradition of Islamic boarding schools in the archipelago, as well as offering an ecospiritual reading of crises that have the potential to strengthen environmental awareness in the pesantren community. مستخلص تتناول هذه الدراسة الاستعارةَ المفهومية في كلمات صلوات بدر من تأليف الشيخ علي منصور، بوصفها تمثيلًا للتجربة الاجتماعية–البيئية في تقاليد البيسانترن وجماعة نهضة العلماء. واعتمدت الدراسة المنهجَ الوصفيَّ النوعي، حيث جُمعت البيانات من ثلاثين سطرًا من النص الشعري تضمّ تعبيراتٍ مجازية على مستوى الكلمة، والعبارة، والجملة. وقد جُمعت البيانات من خلال التوثيق، والقراءة المتأنية، والتدوين، ثم جرى تحليلها بالاستناد إلى نظرية الدلالة المعرفية، وإطار الاستعارة المفهومية عند لاكوف وجونسون، والمقاربة الإيكولغوية (اللسانيات البيئية)، إلى جانب تحليل الثيمة–الريما (Theme–Rheme). وتُظهر نتائج الدراسة وجود سبع عشرة استعارة بنيوية، وستّ استعارات اتجاهية، وسبع استعارات أنطولوجية، تتصل بموضوعات النضال الاجتماعي، والسياسة، والتربية الدينية، والدعاء والتوسل، ورموز نهضة العلماء، وتكامل طقس البرزنجي في السياق الجاوي. ومن منظور إيكولغوي، تُقرأ مفردات مثل «الطاعون» و«الكارثة» بوصفها آثارًا لغويةً لذاكرة الأزمات البيئية والصحية في ستينيات القرن العشرين، ولا سيما تفشّي أمراضٍ مثل الجذام وداء الفيلاريات، وهو ما يكشف عن تنوّع الخطابات الدينية الحافظة للذاكرة الإيكولوجية. وتُظهر نتائج الدراسة وجود سبع عشرة استعارة بنيوية، وستّ استعارات اتجاهية، وسبع استعارات أنطولوجية، تتصل بموضوعات النضال الاجتماعي، والسياسة، والتربية الدينية، والدعاء والتوسل، ورموز نهضة العلماء، وتكامل طقس البرزنجي في السياق الجاوي. ومن منظور إيكولغوي، تُقرأ مفردات مثل «الطاعون» و«الكارثة» بوصفها آثارًا لغويةً لذاكرة الأزمات البيئية والصحية في ستينيات القرن العشرين، ولا سيما تفشّي أمراضٍ مثل الجذام وداء الفيلاريات، وهو ما يكشف عن تنوّع الخطابات الدينية الحافظة للذاكرة الإيكولوجية. وتكتسب هذه الدراسة أهميتها من كونها توسّع آفاق البحث في الاستعارة المفهومية المندمجة بالمقاربة الإيكولغوية في نصوص الصلوات الدينية، ولا سيما في تقاليد المعاهد الإسلامية المنتشرة في أرخبيل إندونيسيا، كما تقدّم قراءةً إيكو-روحية للأزمات بما يحمل إمكانية تعزيز الوعي البيئي داخل مجتمع البيسانترن. Abstrak Penelitian ini mengkaji metafora konseptual dalam lirik Shalawat Badar karya KH Ali Manshur yang merepresentasikan pengalaman sosio-ekologis dalam tradisi pesantren dan Nahdlatul Ulama. Dengan metode deskriptif kualitatif, data diambil dari 30 larik lirik yang memuat ungkapan metaforis pada tataran kata, frasa, dan klausa. Data dikumpulkan melalui dokumentasi, pembacaan cermat, dan pencatatan, kemudian dianalisis dengan teori semantik kognitif, kerangka metafora konseptual Lakoff dan Johnson, pendekatan ekolinguistik, serta analisis tema–rema. Hasil penelitian menemukan 17 metafora struktural, 6 metafora orientasional, dan 7 metafora ontologis yang berkaitan dengan tema perjuangan sosial, politik, pendidikan agama, doa dan permohonan, simbol-simbol Nahdlatul Ulama, serta integrasi ritual Al-Barzanji di Jawa. Dari perspektif ekolinguistik, leksikon seperti “wabah” dan “bencana” dibaca sebagai jejak linguistik dari krisis lingkungan dan kesehatan pada 1960-an, khususnya merebaknya penyakit seperti lepra dan filariasis, sehingga, menunjukkan ragam wacana keagamaan menyimpan memori ekologis. Metafora struktural memosisikan Nabi Muhammad sebagai jembatan mediatif yang menghubungkan komunitas Muslim yang terdampak wabah dan krisis sosial-politik dengan perlindungan ilahi, sementara metafora orientasional memetakan pengalaman spasial ke dalam keadaan emosional dan spiritual. Metafora ontologis memperlihatkan cara agensi ilahi yang abstrak dipahami melalui objek dan peristiwa konkret, dan pola tema–rema menyoroti tema-topik bertanda maupun tak-bertanda yang memajukan narasi krisis dan harapan. Penelitian ini signifikan karena memperluas kajian metafora konseptual yang terintegrasi dengan ekolinguistik pada teks salawat religius dalam tradisi pesantren Nusantara yang sangat populer, serta menawarkan pembacaan ekospiritual atas krisis yang berpotensi menguatkan kesadaran lingkungan dalam komunitas pesantren.